Knowledge, attitudes, perceptions, and practice toward seasonal influenza and its vaccine: A cross-sectional study from a country of conflict - Ahmed, Wesam S.; Abu Farha, Rana; Halboup, Abdulsalam M.; Alshargabi, Arwa; Al-mohamadi, Ahmed; Abu-rish, Eman Y.; Zawiah, Mohammed; Al-Ashbat, Yousf K.; Al-Jamei, Sayida (Frontiers in Public Health, 2023)
Background The seasonal influenza vaccine is an important preventive measure against influenza and its associated complications. In Yemen, there is no seasonal influenza vaccination policy, and the influenza vaccine is excluded from the national immunization program. Data on vaccination coverage remain scarce with no previous surveillance programs or awareness campaigns implemented in the country. The current study aims to assess the awareness, knowledge, and attitudes of the public in Yemen toward seasonal influenza and their motivators and perceived barriers to receiving its vaccine. Methods A cross-sectional survey was carried out using a self-administered questionnaire that was distributed to eligible participants using convenience sampling. Results A total of 1,396 participants completed the questionnaire. The respondents showed a median knowledge score of influenza of 11.0/15.0, and most of them (70%) were able to recognize its modes of transmission. However, only 11.3% of the participants reported receiving the seasonal influenza vaccine. Physicians were the respondents' most preferred information source for influenza (35.2%), and their recommendation (44.3%) was the most cited reason for taking its vaccine. On the contrary, not knowing about the vaccine's availability (50.1%), concerns regarding the safety of the vaccine (17%), and not considering influenza as a threat (15.9%) were the main reported barriers to getting vaccinated. Conclusion The current study showed a low uptake of influenza vaccines in Yemen. The physician's role in promoting influenza vaccination seems to be essential. Extensive and sustained awareness campaigns would likely increase the awareness of influenza and remove misconceptions and negative attitudes toward its vaccine. Equitable access to the vaccine can be promoted by providing it free of charge to the public.